EVALUATION THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN MATHEMATICS LEARNING - Ismail, Nur Ikhsan; Sappaile, Baso Intang; Suhardi, Iwan (Universitas Labuhanbatu, 2025)
Purpose—This research is an evaluative study that aims to evaluate the implementation of the Merdeka curriculum in mathematics learning at SMP Negeri 1 Duampanua.Methodology—The evaluation model used is the CIPP (Contextual, Input, Process, Product) model. The principal, mathematics teachers, and students were the subjects of evaluation in this research. The data collection techniques used were questionnaires, interviews, and documentation. The data analysis technique used was descriptive analysis.Findings – The results of the research indicate that: 1) The Operational Curriculum of the Education Unit (KOSP) at SMP Negeri 1 Duampanua has met expectations, namely by applying the principles of KOSP development, containing the characteristics of the education unit, having a vision, mission, and objectives, regulating learning, planning learning, and planning assistance for evaluation and professional development of educators, 2) The capacity of the educational unit at SMP Negeri 1 Duampanua still needs to be improved and strengthened, 3) The mathematics learning process at SMP Negeri 1 Duampanua has met the established criteria, which include mathematics learning planning, implementation of mathematics learning, and evaluation of mathematics learning, 4) Student learning outcomes in mathematics are in line with the Criteria for Achieving Learning Objectives (KKTP).Significance – This research can contribute to curriculum policy development, especially in implementing the Merdeka Curriculum in mathematics learning in junior high schools. The findings of this study can provide insights for policymakers to evaluate the effectiveness of the curriculum and develop improvement measures, as well as for teachers to improve learning methods that align with the principles of the Merdeka Curriculum. Additionally, the results of this study can help students improve their understanding and motivation in learning mathematics and serve as a reference for further research on the implementation of this curriculum at various levels of education.